PENGARUH ONLINE REVIEW & CUSTOMER EXPERIENCE TERHADAP BRAND IMAGE & PURCHASE INTENTION DI PAINTEREST - Michelle Angelique Maharani; Christina Whidya Utami; Gladys Greselda Gosal (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2021)
Abstract : This study aims to determine the effect of online reviews and customer experiences on brand image and purchasing decisions at Painterest Companies. This study uses a quantitative approach with a sample taken of 210 respondents with a purposive sampling technique which has criteria of people who have used e-commerce shopee, tokopedia and Instagram to make online buying and selling transactions, and have seen Painterest online shop. This research is processed using PLS, with the method of collecting data with a questionnaire using google form. The results of this study indicate that online reviews and consumer experiences have a significant influence on brand image and purchasing decisions at Painterest. The variables studied are interrelated. Having good online reviews and customer experiences creates a good brand image, which will influence purchasing decisions. So, it can be concluded that online reviews and consumer experiences have an effect on brand image and purchasing decisions. Keywords: online review, customer experience, brand image, purchase intention.